Isolation of bacterial fish pathogen Aeromonas hydrophila and therapeutic effects of medicinal plants on its invasion - Md. Tareq-Uz-Zaman; Md. Bazlur Rashid Chowdhury; Md. Rasheduzzaman Khan Dipu (Journal of Fisheries, 2014)
Aeromonas hydrophila, a bacterial pathogen,  was isolated form Pangasius hypophthalmus. For pathogenicity test, different doses were injected intramuscularly in Barbonymus gonionotus. Crude extracts were prepared from various parts Azadirachta indica, Curcuma longa, C. zedoaria, and Callotropis gigentia and applied to B. gonionotus for 7 days. Bath treatment was done up to their tolerance level and well ventilation was confirmed for aeration and 50% water was exchanged daily. Minimum inhibitory dose was detected as 7 mg/ml. High inhibitory effect was observed in case of A. indica and mixed extract of A. indica and C. gigentia. Both A. indica and C. gigentia showed the best result with 90-95% recovery of infected fish at a dose of 7 mg/l. C. zedoaria showed moderate to weak effect with 50-60% recovery at the same dose. The present study showed that medicinal plants would be an effective control measure against A. hydrophila.